Respuesta a la aplicación de tres bioestimulantes foliares en el cultivo de Alfalfa, en la zona de Yahuarcocha, provincia de Imbabura - Salgado Pérez, Luis Ernesto (2012)
This research was conducted in the Yahuarcocha located in Canton Ibarra in Imbabura province. The area is characterized by a Mediterranean-dry, temperate climate with an average temperature of 18 ° C, temperatures may decrease or increase depending on the time of year, so for example the average temperature in January is 7 degrees, while in August can reach 32 degrees. The main objective was to determine the effects of the application of three saw stimulant leaf in alfalfa; Identify foliar stimulant and the proper dosage in order to maximize performance and realize the economic performance analysis considering the cost of treatments.